Potential Use of Insecticides and Mineral Oils for the Control of Transmission of Major Aphid-Transmitted Potato Viruses (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2012)
Viruses occurring in Serbia and other countries in the region are a huge problem constraining seed potato production. At lower altitudes, in lowland and hilly regions, where table potato production is widely distributed, more than 50% of healthy plants become infected with potato virus Y during one growing season. Under these conditions, seed potato production is hindered due to a high infection pressure of potato virus Y which spreads far more rapidly compared to leaf roll virus, virus S and other viruses hosted by this plant species.This study tended to clarify a frequent dilemma regarding the use of insecticides in preventing the infection of healthy plants with potato virus Y and leaf roll virus, given the oral and written recommendations from pesticide manufacturers, agronomists and scientists in the field of crop protection arising from a logical conclusion that aphid vector controlresults in virus transmission control. The present findings, which are in agreement with reports of authors from other countries, show that the use of insecticides is ineffective in preventing potato virus Y which isnonpersistently transmitted by aphids from an external source of infection. However, insecticides can exhibit efficacy in preventing potato virus Y transmission from infected plants to healthy plants within a crop, which can have an overall positive effect only if seed potato is grown in areas that have no external source of infection.The present results and those of other authors show that insecticides are effective in preventing the infection of healthy plants with persistently transmitted leaf roll virus.Mineral oils provide effective control of potato virus Y by preventing the infection of potato plants with the virus. They can be combined with other management practices to protect seed potato crops against the virus. Given the fact that the initial first-year infection of healthy potato plants with virus Y in relation to leaf roll virus is approximately 10-20:1 under conditions in Serbia, and that the use of insecticides fails to ensure protection against PVY, this practice cannot have any positiveeffect on virus control under high infection pressure conditions.
Keywords: Control methods; Vectors; Viruses; Insecticides; Potatoes